Tinjauan Tindak Pidana Human Traficiking sebagai KejahatanTrans-Nasional - Aniek Perian; Rusito (Wijayakusuma Law Review, 2021)
This study aims to review the crime of Human Trafficking as a transnational crime. The author explains theconcept of the crime of Trafficking in Humans which then leads to the condition and development of the crime ofTrafficking in Humans. At the end of the discussion, the author explains how to enforce the law against the crimeof Human Trafficking. The method used in writing this article the author uses a normative juridical researchmethod, where national and international legal sources are used to sharpen the analysis described. Secondarydata obtained from case studies based on cases that occurred in Indonesia. At the end of this article the authorconcludes that social workers need a global perspective to understand the issues that contribute to internationalmigration, including the problems and dynamics of human trafficking.